Academic Libraries and Open Educational Resources: Addressing Student Textbook Affordability - Wilfong, Krystie; Hill, Natalie; Smith, David; Wing, Kate; Spinney, Ann; Koons, Casey (Maine Policy Review, 2024)
College students face a wide number of unexpected financial obstacles in their pursuit of an education – one of the most difficult being the high cost of course materials, such as textbooks. Many textbooks cost more than $200, leading to an additional cost per semester that can approach or exceed $1,000. Facing the costs of housing, food, health care, and other necessities, many students do not purchase needed materials, leading to poor educational performance and outcomes. This commentary explores this issue along with one viable solution – open educational resources (OER), or alternative textbooks and materials for college courses that are free of cost and access barriers through open licensing. These materials are largely produced by faculty in universities. The use and creation of OER has been supported by universities and colleges in Maine and throughout the Northeastern states, with libraries playing a crucial role in both the discovery of existing OER and support in the creation of new materials. We argue that Maine stands poised to take a more active role in the use and creation of OER within our colleges and universities.
Keywords: textbooks; Open Educational Resources